Hukum Vaksin MR: Teori Istihalah dan Istihlak versus Fatwa MUI - Alyasa' Abubakar; Ali Abubakar (Media Syari'ah, 2021)
Measles and rubella are infectious diseases that cause very dangerous diseases throughout the world. Both diseases are incurable; can only be prevented by administering the MR (Measles Rubella) vaccine. However, in Indonesia, the implementation of vaccination for these two diseases did not run smoothly due to the circulation of information that the basic ingredients or the process of making vaccines involved elements of pigs. On that basis, the Indonesian Ulema Council issued Fatwa Number 33 of 2018 concerning the Use of Mr (Measles Rubella) Vaccine Products from SII (Serum Institute Of India) for Immunization which stipulates that "the use of vaccines that utilize pig elements and their derivatives is unlawful". The MUI equates the involvement of pork as the main ingredient and as a medium for making vaccines. This paper relates the fatwa to the prohibition of certain objects in the Qur'an, hadith, and interpretations made by scholars, especially related to the theory of istihālah (perfect change) and istihlāk (mixing). Both of these theories are used in the thought of the scholars of schools and at the present time, especially in objects that are changed through fermentation and synthetic processes, which can be called chemical engineering. Campak dan rubella merupakan penyakit infeksi yang mengakibatkan pernyakit sangat berbahaya  di seluruh dunia. Kedua penyakit tidak dapat diobati; hanya dapat dicegah dengan pemberian vaksin MR (Measles Rubella). Namun demikian, di Indonesia, pelaksanaan vaksinasi untuk kedua penyakit ini tidak berjalan lancar karena beredarnya informasi bahwa bahan dasar atau proses pembuatan vaksin terlibat unsur babi. Atas dasar itu,   Majelis Ulama Indonesia menerbitkan Fatwa Nomor  33 Tahun 2018 tentang Penggunaan Vaksin Mr (Measles Rubella) Produk dari SII (Serum Intitute Of India) untuk Imunisasi yang menentukan bahwa  “penggunaan vaksin yang memanfaatkan unsur babi dan turunannya hukumnya haram”.  MUI menyamakan keterlibatan unsur babi sebagai bahan utama dan sebagai media pembuatan vaksin. Tulisan ini mengubungkan fatwa tersebut dengan keharaman benda tertentu dalam al-Qur'an,  hadis,  dan penafsiran yang dilakukan para ulama, terutama terkait dengan teori istihālah (perubahan sempurna) dan istihlāk (percampuran). Kedua teori ini digunakan dalam pemikiran para ulama mazhab dan pada masa sekarang, terutama sekali pada benda-benda yang berubah melalui proses fermentasi dan sintetis, yang dapat disebut sebagai rekayasa kimiawi.